Implant survival and functional results of endoprosthetic reconstruction for proximal femoral metastases with pathological fractures - EROL, BÜLENT; ŞİRİN, EVRİM; İĞREK, SERVET (SAGE PUBLICATIONS LTD, 2022)
Background: This study aimed to evaluate the patient and implant survival, clinical and functional outcomes, and the rate of complications resulting in reconstruction failure following endoprosthetic reconstruction (EPR) of extensive proximal femoral metastases associated with actual or impending pathological fractures. Methods: A total of 111 patients with actual or impending pathological fractures due to metastatic disease of the proximal femur were treated with EPR between 2003 and 2018. Staged surgery, bilateral EPR, was performed in 3 cases. The patients comprised 51 females and 60 males with a mean age of 52.1 +/- 12.3 years. The patient and implant survival were recorded. Clinical and functional outcomes were assessed by using the visual analogue scale (VAS), Musculoskeletal Tumour Society (MSTS) functional scoring, and Karnofsky Performance Scale (KPS). The different types of abductor mechanism repair were evaluated by functional tests and existence of Trendelenburg gait at postoperative follow-ups. The complications resulting in reconstruction failure were investigated. Results: The mean follow-up was 23.1 +/- 17.9 months. The overall survival of patients after EPR was 89% at 6 months, 72% at 1 year and 10% at 5 years. The estimated 1- and 5-year overall implant survival was 100% and 97.3% (95% CI, 0.95-0.98), respectively, as the endpoint was defined as complete removal of the prosthesis. Median VAS score before endoprosthetic replacement was 8 and after 3 months 4. Before surgery, the median MSTS score was 40 (30-56.6%) and the median KPS score was 40 (30-50). Postoperative third month, the median MSTS score was 56.6 (53.3-86.6%) and the median KPS score was 60 (40-70). Functional scores were superior in trochanter major split osteotomized group compared to trochanter major removed group. Trendelenburg gait was seen in 20 (17.5%) patients postoperatively. There were 10 (8.7%) complications resulting in reconstruction failure. Conclusion: Endoprosthetic replacement can provide a durable fixation with high implant survival rate and good clinical and functional results in extensive proximal femoral metastases associated with a pathological fracture.
Keywords: Bone metastasis; endoprosthetic reconstruction; pathological fracture; proximal femur; survival; SURGICAL-TREATMENT; BONE METASTASIS; FEMUR; DISEASE; SALVAGE; LESIONS